Internet of things forensic: contemporary issues, challenges, and future research directions - Altaha, Safa; M. Hafizur Rahman, M. (Bulletin of Electrical Engineering and Informatics, 2025)
The internet of things (IoT) comes with great capabilities as well as new opportunities for attackers and criminals. Even though digital forensics is considered to be mature and has been studied by many researchers in recent years, IoT forensics is relatively new and yet to be thoroughly explored. IoT technology has unique characteristics that require adoption of the traditional digital forensic approaches, frameworks, and tools. The primary goal of IoT forensics is to collect, preserve, and present evidence in a manner that meets legal standards and country law from a specific IoT system that includes connected devices and sensors via different types of networks and associated cloud environments. In this paper, we explored the main difference between IoT forensics and traditional digital forensics. This paper aims to provide a comprehensive and up-to-date overview of recently proposed solutions for addressing the IoT forensic domain. we highlighted the limitations of the recently proposed framework and the utilized technologies by researchers. In addition, we recommended some new research directions that could enhance the IoT investigation process. The goal of this paper is to provide a clear understanding of the currently used technologies and other fields in IoT forensic frameworks, limitations, and directions in this area, which may be helpful for future researchers interested in this field.